Sinergitas Kementerian dan Lembaga dalam Mengantisipasi Konflik di Laut China Selatan - Setiowati, Renny; Jati, Sundring Pantja; Widodo, Puji; Suharjo, Bambang (Universitas Trunojoyo Madura, 2021)
The South China Sea is one of the epicenters of conflict in the 21st century. The South China Sea area includes waters and land located in the archipelago of two large islands, namely the Spratlys and Paracels, as well as the banks of the Macclesfield and Scarborough Reef Rivers which stretch from Singapore, from the Malacca Strait to the Taiwan Strait. As this vast territory has often been subjected to successive control by neighboring rulers, several countries, such as the People's Republic of China (PRC), Taiwan, Vietnam, the Philippines, and Brunei Darussalam, have engaged in confrontational attempts to claim, over large parts of the entire territory. . While on the one hand Indonesia supports the prospect of peace in the South China Sea for economic development and domestic stability, Indonesian policymakers are concerned about China's interpretation of its South China Sea claims, which also includes reserves of natural gas and other natural resources. inside it. On the other hand, Indonesia is committed to defending the rights of the archipelagic state as stated in UNCLOS.